The French New Towns - Rubenstein, James M. (Johns Hopkins University Press, 2019)
Originally published in 1978. At the time this book was published, new towns were cropping up as a matter of public policy in "advanced industrial countries," yet the United States abandoned this project and deemed new towns "inappropriate and impractical for the American situation." The purpose of this book is to inform planners and policy makers around the world about French new towns. It analyzes what French new towns tried to accomplish; the administrative, financial, and political reforms needed to secure implementation of the program; and the achievements of the new towns. The author's evaluation of French new towns is undertaken with an eye to international applicability.In the United States, new towns have been proposed as a means for integrating low-income families into suburbs that are otherwise closed to them. The French experience demonstrates that socially heterogeneous new communities can be developed, even within the framework of a market system, if a sufficiently high priority is placed on the effort.